Perceptual model-based information hiding in audio signals - Khalifa, Othman Omran; Mahmoud, Omer; Khan, Sheroz (2012)
Audio data hiding is the process of embedding information into an audio signal so that the embedded information is inseparable from it and imperceptible to the listener. Information hiding is a multi- disciplinary area that combines signal processing with cryptography, communication theory, coding theory, information theory and the theory of human auditory and visual systems where information is hided within a host signal. A data hiding system should be robust, meaning that the embedded data could be decoded from the combined signal, even if it is distorted or attacked. This paper examines information hiding in speech signals. A perceptual modelbased information hiding in speech signal is developed.